Strategic and practical approaches for information security governance technologies and applied solutions - Gupta, Manish 1978-; Walp, John; Sharman, Raj (Information Science Reference, 2012)
"This book provides organizations with insights into practical and applied solutions, frameworks, technologies and practices on technological and organizational factors in information security" - Provided by publisher
Includes bibliographical references
Keywords: Computer networks / Security measures; Information networks / Security measures; Data protection / Security measures; Aufsatzsammlung